What is the current clinical practice in pituitary adenoma surgery in Europe? European Pituitary Adenoma Surgery Survey (EU-PASS) results-technical part - Májovský, Martin; Grotenhuis, Andre; Foroglou, Nicolas; Zenga, Francesco; Froehlich, Sebastien; Ringel, Florian; Sampron, Nicolas; Thomas, Nick; Komarc, Martin; Netuka, David (Neurosurgical review, 2022)
Pituitary adenoma surgery has evolved rapidly in recent decades, changing clinical practice markedly and raising new challenges. There is no current consensus or guidelines for perioperative care that includes possible complication management. This study aims to determine current practice across European neurosurgical centres. We created a list of eligible departments performing pituitary adenoma surgery based on cooperation with EANS, national neurosurgical societies, and personal communication with local neurosurgeons. We contacted the chairpersons from each department and asked them (or another responsible neurosurgeon) to fill out the survey. The survey consisted of 58 questions. For further analysis, departments were divided into subgroups: "academic"/ "non-academic centre", "high-volume"/"low-volume", "mainly endoscopic"/ "mainly microscopic"/ "mixed practise", and by geographical regions. Data from 254 departments from 34 countries were obtained. The average time to complete the survey was 18 min. Notably, the endoscopic approach is the predominant surgical approach in Europe, used in 56.8% of the centres. In routine cases without intraoperative cerebrospinal fluid leak, high-volume centres are less pedantic with sellar closure when compared with low-volume centres (p < 0.001). On the other hand, when a postoperative cerebrospinal fluid leak occurs, high-volume centres are more active and indicate early reoperation (p = 0.013). Less than 15% of the participating centres perform early postoperative MRI scans. Marked variation was noted among different groups of respondents and some contentious issues are discussed. Such information can encourage useful debate about the reasons for the variations seen and perhaps help develop standardised protocols to improve patient outcomes. A future research focus is to compare European results with other regions.
Keywords: Adenoma; Pituitary Neoplasms; Neurosurgery; adenom; Endocrinology; únik mozkomíšního moku; nádory hypofýzy; endoskopie; Endoscopy; retrospektivní studie; lidé; Retrospective Studies; Cerebrospinal Fluid Leak; Surveys and Questionnaires; Pituitary adenoma; Humans; průzkumy a dotazníky; Survey